DIAGNOSIS OF STRUCTURE FORMATION KNOWLEDGE OF A FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2022)
The questions related to forming and diagnostics of "normative" structure o f knowledges are examined in the article. Under "normative" knowledges knowledges, which respond to nufuest, which are subject to the obligatory mastering and subsequent control from the side of educational establishments state educational standard, are understood. On the basis of the conducted researches of grounded, that the test control is the most objective form of diagnostics of the formed structure of knowledges.